The Influence of the Gemification Method on Vocabulary Development in Primary Schools - Santoso, Titah Agastya; Armeridha, Yesika Agnes Sandya; Pradana, Dian Arief (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
English in Indonesia is studied as a foreign language since school age to help prepare the younger generation to face the global world. However, the uneven education system in cities and rural areas is one of the challenges in teaching English to students. As a result of this challenge, students' motivation to learn English is low because it is considered boring and difficult to learn. The difference in English language skills of elementary school children in urban and rural areas is the reason for the implementation of this English language training service program for elementary school students. This program aims to improve English skills, especially vocabulary development and speaking skills for elementary school students. Teaching using the gamification method is an option that is considered effective for teaching and training students to learn English because it can increase children's interest and motivation through playing snakes and ladders, guessing words, and singing. The data collection techniques used are participant observation, pre-test, and post-test.